2003
DOI: 10.1046/j.1365-201x.2003.01161.x
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator‐activated receptors (PPARS): regulators of gene expression in heart and skeletal muscle

Abstract: The peroxisome proliferator-activated receptors (PPARs) are members of the nuclear hormone receptor superfamily. The three isoforms (PPARalpha, beta/delta and gamma) have been implicated in the regulation of the expression of genes involved in lipid metabolism. Although their prominent role in lipid homeostasis is well established, the way in which the activity of each of the PPAR isoforms is regulated under physiological and pathological conditions is still subject of intensive research. In skeletal as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
123
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(130 citation statements)
references
References 91 publications
5
123
0
2
Order By: Relevance
“…The AMPK dependent phosphorylation of PGC-1α additionally is associated with an increase in the expression of mitochondrial genes [28]. As we mentioned PGC-1α acts as a transcriptional co-activator where it moderates the activity of multiple transcription factors including the PPAR's (PPAR-γ, PPAR-α and PPAR-δ), mitochondrial transcription factor A (TFAM), nuclear respiratory factors 1/2 (NRF1/2) and estrogen related receptor-α (ERR-α) (Figure 1) [32]. The PPAR's are also of interest with regard to nutritional interventions as they are sensitive to changes in fatty acid levels in that increased free fatty acid (FFA) availability leads to increases in the activity of these transcription factors which control the expression of FFA metabolism genes [33].…”
Section: The Molecular Regulation Of Endurance Training Adaptation Ementioning
confidence: 93%
“…The AMPK dependent phosphorylation of PGC-1α additionally is associated with an increase in the expression of mitochondrial genes [28]. As we mentioned PGC-1α acts as a transcriptional co-activator where it moderates the activity of multiple transcription factors including the PPAR's (PPAR-γ, PPAR-α and PPAR-δ), mitochondrial transcription factor A (TFAM), nuclear respiratory factors 1/2 (NRF1/2) and estrogen related receptor-α (ERR-α) (Figure 1) [32]. The PPAR's are also of interest with regard to nutritional interventions as they are sensitive to changes in fatty acid levels in that increased free fatty acid (FFA) availability leads to increases in the activity of these transcription factors which control the expression of FFA metabolism genes [33].…”
Section: The Molecular Regulation Of Endurance Training Adaptation Ementioning
confidence: 93%
“…Tiwari et al (1991) reported a relationship between ERBB2, fatty acids and 2 0 ,5 0 oligoadenylate synthetases (OAS2), which is included in our 'ERBB2 cluster'. Peroxisome proliferator-activated receptors (PPARs) are known regulators of lipid metabolism; their trans-activating capacity depends on the recruitment of auxiliary proteins (for a review, see Gilde and van Bilsen, 2003); modifications of fatty acid metabolism in ERBB2 þ tumours may thus be simply associated with overexpression of PPARBP.…”
Section: Erbb2 and Microarraysmentioning
confidence: 99%
“…It cooperates with transcription factor PGC1, overexpression of which has been demonstrated to enhance both lipid oxidation and synthesis (Espinoza et al 2010). Another possibility is that palmitate is a ligand for the transcription factors involved in the regulation of cell´s oxidative capacity, such as PPAR (Gilde & Van Bilsen 2003). Animal (Hancock et al 2008) as well as clinical studies (Bajaj et al 2007) also support the role of fatty acids for PGC1 regulation at the level of gene expression.…”
Section: Mitochondrial Biogenesis In Muscle Cells -Lipids and Exercisementioning
confidence: 87%
“…Fatty acids are known to be the ligands of various transcription factors involved in the regulation of metabolism and mitochondrial biogenesis (Gilde & Van Bilsen 2003). It has been shown previously that fatty acids as well as a diet with an increased fat content is capable of inducing mitochondrial biogenesis both in vitro and in vivo (Watt et al 2006;Hancock et al 2008).…”
Section: Mitochondrial Biogenesis In Muscle Cells -Lipids and Exercisementioning
confidence: 99%